Pengaruh Asosiasi Merek, Kualitas Produk, dan Loyalitas terhadap Keputusan Menabung di BSI Kota Palu : (Studi Pada BSI KCP Gajah Mada) - Dela Puspita; Arlisa Arlisa; Dicki Wahyudi; Muh. Husnil; Ansar Ansar; Sitti Aisya; Rizki Amalia (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study aims to deeply analyze the effect of brand association, product quality, and customer loyalty on saving decisions at Bank Syariah Indonesia (BSI) KC Gajah Mada, Palu City. With a focus on customer behavior, this research also seeks to understand how these three factors interact with each other and contribute to shaping savings decisions at Islamic banks. The method used in this research is a quantitative approach with a survey design to obtain objective and measurable data. The research sample consisted of 98 respondents selected by purposive sampling, namely with certain criteria relevant to the research objectives. The results showed that the brand association variable had no significant effect on saving decisions at Bank Syariah Indonesia KC Gajah Mada, Palu City. In contrast, the variables of product quality and customer loyalty are proven to have a significant influence on saving decisions. Simultaneously, the three variables together have a significant influence on saving decisions. This is reinforced by the results of the F test which shows the calculated F value of 69.100, which is greater than the F table of 3.94, with a significance level of 0.001, which means that the regression model used is feasible and these variables contribute significantly in explaining the customer's saving decision. The implication of this research for BSI is to strengthen brand association and improve product quality and pay attention to customer loyalty. For students, this research can be a reference in Islamic banking studies, and for future researchers it is recommended to add other variables to enrich the analysis.